18F-FDG pet to evaluate treatment response and relapse in patients presenting with clinically manifest cardiac sarcoidosis - Reis, Christiane Cigagna Wiefels (2024)
Introduction: Cardiac involvement can be the first manifestation of sarcoidosis, even in patients with systemic disease. Positron emission tomography (PET) imaging is an essential diagnostic tool as it can detect active disease but is also helpful in guiding therapy by detecting non-responsiveness or relapse. With the absence of randomized trials, first-line treatment with corticosteroids has been recommended by most experts during the past 50 years, but it is unknown if all patients should be treated nor for how long. We aimed to evaluate to evaluate the capacity of 18FDG PET to systematically and prospectively (i) assess the response to corticosteroids and (ii) to assess the incidence of relapse after a one-year course of corticosteroids (thereby classifying patients as acute or chronic phenotype). Methods: Consecutive newly diagnosed, treatment-naive patients with clinically manifest cardiac sarcoidosis and a baseline PET (PET 1) were prospectively recruited. All patients were treated with 0.5 mg/kg prednisone up to a maximum dose of 40mg OD. All patients had a follow-up PET 2 scan after 3-6 months of therapy. Patients were then classified as responders or non-responders. The prednisone was then weaned over six months in the responders and stopped. Three months after stopping, the PET was repeated to look for disease relapse (PET 3). Multiple clinical and imaging parameters were analyzed. Results: Twenty-one patients were recruited. The mean age at presentation was 55.9  8.5 years old, and ten were female. On PET 2, 19 patients responded to steroids, and after therapy discontinuation, 12 relapsed, being considered chronic. The other seven were classified as having an acute phenotype. The mean increase in LV SUVmax from PET 2 to PET 3 in the relapse group was 5.06 ± 3.05 (p < 0.001), with a mean percentage increase of 164.4 ± 132.3 %. No clinical or imaging findings could predict which patients would have a relapse. Conclusion: Our findings suggest that the use of serial PET scanning can guide the treatment of clinically manifest cardiac sarcoidosis and identify a subset of patients who do not require chronic treatment.